An inventory hub location model for multi‐coal‐fired coastal power plants: a case study in Guangdong district. (3rd January 2022) - Han, Peixiu; Sun, Zhuo; Liu, Zhongbo
Abstract: The increasing demand for electric power is an established trend in China, of which coal power accounts for a large proportion. This paper proposes an inventory hub location model considering multi‐type coal to minimize the total transportation and inventory cost in a multi‐coal‐power supply chain. A second‐order cone programming method is adopted to convert the original model. The exact solutions of the small‐scale real case show that the model can greatly reduce the total costs by CPLEX. For real‐world large‐scale cases, a customized greedy randomized adaptive search simulated annealing algorithm is devised and tested to obtain near‐optimal solutions within a reasonable time. The research has strong practical guiding significance for the management of the thermal coal supply chain.